Inventando numeros - Rodari, Gianni; Sanna, Alessandro, 1975- (Sevilla : Kalandraka, 2007)
Two friends have fun inventing numbers while rhyming.
Keywords: Counting -- Juvenile fiction; Stories in rhyme; Numeracion -- Novela juvenil; Cuentos en rima